A study on using expanded perlite with hydroxyapatite: Reinforced bio-composites - Karip, Erdogan; Muratoglu, Mehtap (Sage Publications Ltd, 2021)
People are exposed to different kinds of diseases or various accidents in life. Hydroxyapatite (HA) has been widely employed for bone treatment applications. In this study, HA was extracted from sheep bones. Bio-composites were doped with 1, 5, and 10 wt.% of expanded perlite and 5 wt.% of ZrO2-MgO-P2O5. The bio-composites were prepared by the cold isostatic pressing method (250 MPa) and sintered at 900 degrees C for 1 h. In order to evaluate the characteristics of the bio-composites, microhardness, density, X-ray diffraction (XRD), Fourier transform infra-red spectroscopy (FT-IR), scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS) analyses were carried out on them. Additionally, the specimens whose characteristics were determined were kept in synthetic body fluid (SBF), and their in vitro behavior was examined. As a result, it was observed that microhardness increased as both the weight and the grain size of the expanded perlite were increased. Calcium silicate, tri-calcium phosphate, and hydroxyapatite were observed in the XRD analysis of all samples, and the formation of apatite structures was increased by addition of ZrO2-MgO-P2O5.
Keywords: Sheep hydroxyapatite; expanded perlite; ZrO2; MgO; P2O5